MAGNITUDE AND PATTERN OF INJURIES IN PATIENTS VISITING ACCIDENT AND EMERGENCY DEPARTMENT OF COMBINED MILITARY HOSPITAL, RAWALPINDI - A CROSS SECTIONAL STUDY - Hamid Jamal Siddique (Army Medical College Rawalpindi, 2020)
Objective: To determine the magnitude and pattern of injuries and their associated contributory risk factors in patients visiting accident and emergency department.